PENGARUH KOMUNIKASI GURU DAN ORANG TUA TERHADAP HASIL BELAJAR MATEMATIKA PECAHAN SISWA KELAS IV SD - Mahdavikia; Mohamad Syarif Sumantri; Engga Dallion EW (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to investigate the influence of communication between teachers and parents on the learning outcomes of fraction mathematics for fourth-grade students at SDIT Baiturahman Citra, West Jakarta. The research employed a quantitative correlational method with a total sample of 40 students. Data were collected through questionnaires on teacher-parent communication and tests on fraction mathematics learning outcomes. Data analysis was conducted using the Shapiro-Wilk normality test and Spearman correlation test due to non-normal data distribution. The results show that teacher-parent communication is categorized as very high based on students' perceptions, while the learning outcomes in fraction mathematics fall into the good category. However, the correlation test indicated no significant relationship between teacher-parent communication and students’ fraction mathematics learning outcomes (r = -0.105; p = 0.517). This suggests that although communication runs very well, it does not have a direct impact on improving students’ learning outcomes in fractions. The study recommends that schools and parents maintain effective communication and develop more varied teaching methods to enhance students’ learning achievements.